Pragmatic Function Shifts in the Translation of WH Questions in “500 Days of Summer” - Prahara, Muhammad Afrizal Lutfi (Universitas Sebelas Maret, 2021)
The author is analyzing and conducting a translation research in interrogative utterances from the film